2021
DOI: 10.1016/j.jinf.2021.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Co-infections and superinfections complicating COVID-19 in cancer patients: A multicentre, international study

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
30
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 33 publications
5
30
1
1
Order By: Relevance
“…[ 55 – 57 ], late infections after intubation [ 55 ], and recovery of multidrug-resistant pathogens [ 58 ]. These also extend results to a wider geographic area including South America [ 56 ] and the Middle East [ 59 ], as well as patient populations such as cancer patients [ 60 ] and postmortem studies [ 57 ]. An Italian paper showed bronchoalverolar lavage from 24 critically ill COVID-19 patients tended to grow gram-negative bacteria "predisposed to multidrug resistance" while 24 matched non-COVID-19 controls had more commensal flora such as Haemophilus sp.…”
Section: Discussionsupporting
confidence: 62%
“…[ 55 – 57 ], late infections after intubation [ 55 ], and recovery of multidrug-resistant pathogens [ 58 ]. These also extend results to a wider geographic area including South America [ 56 ] and the Middle East [ 59 ], as well as patient populations such as cancer patients [ 60 ] and postmortem studies [ 57 ]. An Italian paper showed bronchoalverolar lavage from 24 critically ill COVID-19 patients tended to grow gram-negative bacteria "predisposed to multidrug resistance" while 24 matched non-COVID-19 controls had more commensal flora such as Haemophilus sp.…”
Section: Discussionsupporting
confidence: 62%
“…Most immunosuppressed patients receive empiric antibacterial or antifungal agents, which can lead to high costs, side effects, drug–drug interactions, and development of resistance. In a previous report from Europe, North America, and South America, >80% of patients with cancer and COVID-19 received empiric antimicrobials, although only 8% had another infection at the time of COVID-19 diagnosis, and 19% developed secondary infections [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with cancer are vulnerable to infection due to myelosuppression and other forms of direct immune suppression caused by cytotoxic chemotherapy or chronic steroids, side effects of chemotherapy on mechanical barriers (eg, mucositis and skin ulceration), presence of indwelling central venous catheters, and increased exposure to health care facilities [ 8 ]. One study of 684 patients with cancer focused on coinfections showed higher incidence compared with the general population [ 5–7 , 9 ].…”
mentioning
confidence: 99%
“…Table 3 summarizes single cases of COVID-19 hematologic cancer patients with fungal co-infections. Very recently, a multicenter cohort study of cancer patients with COVID-19 describing the epidemiology, risk factors, and clinical outcomes of co-infections and super-infections has been published [100]. In this large series, hematologic patients represent 43.8% of all cancer patients enrolled.…”
Section: Hematological Malignanciesmentioning
confidence: 99%